L’analyse de l’activité dans les situations sportives par l’articulation de données hétérogènes : Réflexions et perspectives au service de l’ingénierie de conception - David Adé; Nathalie Gal-Petitfaux; Nadège Rochat; Ludovic Seifert; Olivier Vors (Activités)
This article examines the expansion of methodologies for articulating heterogeneous (experiential and behavioral) data within the course-of-action research program (Theureau, 2004, 2006, 2009, 2015). In the area of sports expertise, recent studies have articulated verbalizations based on conscious awareness and behavioral data from largely unconscious processes in order to shed light on expert instrumented activity. The methodological differences between these studies are highlighted, especially regarding the priority given to the types of data and the conditions under which these data were collected. Three studies are presented, covering trail running, swimming, and ice climbing, and each is distinct in its conditions for data collection and processing and its methodology for data articulation. We examine their advantages and limitations for aiding the design of sports equipment and question the observatory within the course-of-action research program. Essentially, the program’s methodological advances raise questions about how sports equipment is designed, the athlete-researcher-designer relationship, and the heuristic scope for analyzing activity in work situations that share similarities with the instrumented activity of sports situations.